Maternofetal consequences of Coxiella burnetii infection in pregnancy: a case series of two outbreaks - Boden, Katharina; Junghanss, Thomas (BMC infectious diseases, 2012)
A high complication rate of Q fever in pregnancy is described on the basis of a limited number of cases. All pregnant women with proven Q fever regardless of clinical symptoms should therefore receive long-term cotrimoxazole therapy. But cotrimoxazole as a folic acid antagonist may cause harm to the fetus. We therefore investigated the Q fever outbreaks, Soest in 2003 and Jena in 2005, to determine the maternofetal consequences of Coxiella burnetii infection contracted during pregnancy.